Pengaruh Bahasa Melayu dalam Pembentukan Bahasa Indonesia - Alika Adelia; Dewi Annisa; Marlenny Fuji Ayu; Revalina Novianti Ridwan; Ahmad Fu'adin (UNIVERSITAS SERAMBI MEKKAH, 2025)
The Malay language has been used as a lingua franca since the 7th century during the Sriwijaya and Malacca Continentals. The Malay language spread rapidly because it was influenced by the trade and education sectors at that time. The method used in this research is the literature review method with literature study, namely reading written sources through journals, articles, and research reports as well as in-depth analysis of the influence of the Malay language in the formation of the Indonesian language which aims to examine the formation of the Indonesian language influenced by the Malay language. As for the results of the research that the Malay language became the basis for the formation of the Indonesian language, through the youth oath in 1928, the official Malay language as the basis for the birth of the language of unity, namely the Indonesian language which is used in organization, education, and the purpose of fighting the invaders. To maintain the existence of the Indonesian language, congresses were held so that the Indonesian language would continue to maintain its development.